Adaptation of H(+)-Pumping and Plasma Membrane H(+) ATPase Activity in Proteoid Roots of White Lupin under Phosphate Deficiency - Yan, Feng (American Society of Plant Physiologists, 2002)
White lupin (Lupinus albus) is able to adapt to phosphorus deficiency by producing proteoid roots that release a huge amount of organic acids, resulting in mobilization of sparingly soluble soil phosphate in rhizosphere. The mechanisms responsible for the release of organic acids by proteoid root cells, especially the trans-membrane transport processes, have not been elucidated. Because of high cytosolic pH, the release of undissociated organic acids is not probable. In the present study, we focused on H(+) export by plasma membrane H(+) ATPase in active proteoid roots. In vivo, rhizosphere acidification of active proteoid roots was vanadate sensitive. Plasma membranes were isolated from proteoid roots and lateral roots from P-deficient and -sufficient plants. In vitro, in comparison with two types of lateral roots and proteoid roots of P-sufficient plants, the following increase of the various parameters was induced in active proteoid roots of P-deficient plants: (a) hydrolytic ATPase activity, (b) V(max) and K(m), (c) H(+) ATPase enzyme concentration of plasma membrane, (d) H(+)-pumping activity, (e) pH gradient across the membrane of plasmalemma vesicles, and (f) passive H(+) permeability of plasma membrane. In addition, lower vanadate sensitivity and more acidic pH optimum were determined for plasma membrane ATPase of active proteoid roots. Our data support the hypothesis that in active proteoid root cells, H(+) and organic anions are exported separately, and that modification of plasma membrane H(+) ATPase is essential for enhanced rhizosphere acidification by active proteoid roots.